Abundance, Distribution Patterns and Habitat Conditions of Giant Clam (Family : Tridacnidae) - Iriansyah Iriansyah; Ricardo F. Tapilatu; Hendri Hendri (Musamus Fisheries and Marine Journal, 2021)
The Giant Clam has a high economic value it is because all parts of the animal can be utilized so it is very vulnerable for hunting by humans. Traditionally these animals are used by people for food, building materials, household needs and as souvenirs and also as aquarium animals. The purpose of this study is to see the relationship between species abundance and distribution patterns of Giant Clam based on the habitat conditions. Moreover, the purpose of this study case is to identify the types of Giant Clam that found and compare with research which has been done 10 years earlier. The results of the data analysis concluded that habitat conditions take effect on species abundance and distribution patterns of Giant Clam on Mansinam Island and Lemon Island in Manokwari Regency. From the results of the study found 3 types of Giant Clams with a total of 14 individuals. The number of Giant Clam species that found at the study location is almost half of the species that found in Indonesia. For 10-year period at the study location there was decrease the number of Giant Clam species by 57%, in 2009 there were found 7 species of Giant Clam whereas in 2019 only found 3 species of Giant Clams.